2019
DOI: 10.3390/nu12010063
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Crossover Trial Assessing the Safety and Short-Term Effects of Walnut Consumption by Patients with Chronic Kidney Disease

Abstract: The aim of this study of patients with chronic kidney disease (CKD) is to assess the safety of daily consumption of walnuts on the physiological levels of phosphorous, potassium, parathyroid hormone (PTH), and fibroblast growth factor 23 (FGF23), and to assess the short-term benefits of this intervention on risk factors associated with cardiovascular events. This led us to perform a prospective, randomized, crossover, pilot clinical trial examined 13 patients with CKD. Subjects were randomly assigned to a diet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The results remained statistically significant after performing a leave-one-out sensitivity analysis for each study. The studies that influenced the final result the most were Tapsell et al (2009) [ 36 ] and Abdrabalnabi et al [ 45 ]; their removal brought the I 2 to values lower than or equal to 7%. A subgroup analysis found that studies with a high risk of bias had higher reductions in TG values than studies with some concerns or low risk of bias, the pooled result remaining statistically significant only for high risk of bias studies ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results remained statistically significant after performing a leave-one-out sensitivity analysis for each study. The studies that influenced the final result the most were Tapsell et al (2009) [ 36 ] and Abdrabalnabi et al [ 45 ]; their removal brought the I 2 to values lower than or equal to 7%. A subgroup analysis found that studies with a high risk of bias had higher reductions in TG values than studies with some concerns or low risk of bias, the pooled result remaining statistically significant only for high risk of bias studies ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another limitation is the follow-up period, which ranged from 4 weeks to 2 years and, therefore, longterm effects (i.e., years) of walnut consumption on BP cannot be estimated. Only two included studies were carried out on a ≥1 year follow-up (Al Abdrabalnabi et al, 2020;Sanchis et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 17 articles with 18 comparisons were included in this meta-analysis ( Figure 1). Abdrabalnabi et al, 2020;Katz et al, 2012;Ma et al, 2010;Njike, Ayettey, Petraro, Treu, & Katz, 2015;Rock, Flatt, Barkai, Pakiz, & Heath, 2017;Spaccarotella et al, 2008;Tindall et al, 2019), Republic of Korea (Hwang et al, 2019), Australia (Ndanuko, Tapsell, Charlton, Neale, & Batterham, 2018), Iran (Fatahi, Haghighatdoost, Larijani, & Azadbakht, 2019;Nezhad, Aghasadeghi, Hakimi, Yarmohammadi, & Nikaein, 2016), United Kingdom (Din et al, 2011), Spain (Olmedilla-Alonso et al, 2008;Ros et al, 2004;Sanchis et al, 2019), Chine (Wu et al, 2010), and New Zealand (Mukuddem-Petersen, Stonehouse Oosthuizen, Jerling, Hanekom, & White, 2007). The follow-up period ranged from 4 weeks to 2 years.…”
Section: Study Selectionmentioning
confidence: 99%
“…Eight of the RCTs were parallel group studies, 63 , 64 , 78 , 79 , 82–89 , 92–94 and 5 employed a crossover design. 65 , 80 , 81 , 90 , 91 , 95–97 RCTs were conducted in Australia, Cyprus, Germany, Iran, South Korea, Spain, Tunisia, Turkey, and the United States. The number of enrolled subjects ranged from 15 to 708, and study duration ranged from 3 weeks to 2 years.…”
Section: Resultsmentioning
confidence: 99%